EFFECTIVENESS OF IMPLEMENTATION ENRICHMENT MODELRENZULLI TYPE III TO INCREASE LEARNING OUTCOME HIGH ACHIEVING STUDENTS GRADE V IN SD 1 TRIRENGGO AT THEME 8 THE MATTER OF SCIENCES - Saputri Diah; Rochmat Wahab (JPK (Jurnal Pendidikan Khusus), 2019)
This research aimed to examine the effectiveness of implementation Enrichment Model Renzulli Type III to increase learning outcome high achieving students grade V in SD 1 Trirenggo at theme 8 the matter  of IPA. This research used quantitative approach with quasi experimental research type. The research design used was one group pretest-posttest design. The subjects of the study used three high achieving science students of grade V elementary school. Data collection using tests, observations, and documentations. Analysis of data used using non parametric statistics Type Wilcoxon Sign Rank Test. The results of the Wilcoxon Sign Rank Test results obtained T count = 0 (α = 0,05), then T count ≤ Tα and H0 rejected and Ha accepted. This means that Enrichment Model Renzulli Type III is effective to improve learning outcome of the high achieving science students of class V elementary school in SD 1 Trirenggo. The effectiveness of Enrichment Model Renzulli Type  III is indicated by an increase in the score of pre-test and post-test results. The average pre-test score is 45 and average post-test score is 74.67. Where there is a score increase of 29.67%.